Strategi Peningkatan Kinerja Karyawan - Triemiaty, Triemiaty; Maarif, Muhammad Syamsul; Affandi, Muhammad Joko; Pawenary, Pawenary (Benefit: Jurnal Manajemen dan Bisnis, 2019)
The purpose of this study was to examine and (1) analyze the influence of organizational culture on employee performance (2) analyze the effect of job satisfaction on employee performance (3) analyze the effect of work safety on employee performance (4) analyze the influence of organizational culture, job satisfaction, and work safety on employee performance and (5) formulate a strategy to improve employee performance that is appropriate to be implemented in PT Bakrie Construction. The selected respondents were employees of PT Bakrie Construction. In this case the researcher took a sample of 115 respondents. Data analysis techniques using Structural Equation Model-Partial Least Square (SEM-PLS) and to determine the performance improvement strategy used Analysis Hierarchy Process (AHP). The results of this study indicate that (1) Organizational culture does not significantly influence employee performance, but indirectly affects performance through job satisfaction. (2) Job satisfaction has a significant effect on employee performance (3) Occupational safety has a significant effect on employee performance (4) Job satisfaction together has a significant effect on employee performance. Organizational culture does not significantly influence performance, but indirectly affects employee performance through job satisfaction (5) The alternative strategy that can be done by PT Bakrie Construction in improving employee performance is to improve the welfare of its employees.